Cardiopulmonary exercise testing in the MRI environment. (14th March 2016) - Lafountain, Richard A; da Silveira, Juliana Serafim; Varghese, Juliet; Mihai, Georgeta; Scandling, Debbie; Craft, Jason; Swain, Carmen B; Franco, Veronica; Raman, Subha V; Devor, Steven T; Simonetti, Orlando P
Abstract: Maximal oxygen consumption ( max) measured by cardiopulmonary exercise testing (CPX) is the gold standard for assessment of cardiorespiratory fitness. Likewise, cardiovascular magnetic resonance (CMR) is the gold standard for quantification of cardiac function. The combination of CPX and CMR may offer unique insights into cardiopulmonary pathophysiology; however, the MRI-compatible equipment needed to combine these tests has not been available to date. We sought to determine whether CPX testing in the MRI environment, using equipment modified for MRI yields results equivalent to those obtained in standard exercise physiology (EP) lab. Ten recreationally trained subjects completed max tests in different locations; an EP laboratory and an MRI laboratory, using site specific equipment. CMR cine images of the heart were acquired before and immediately after maximal exercise to measure cardiac function. Subjects in all tests met criteria indicating that peak exercise was achieved. Despite equipment modifications for the MRI environment, max was nearly identical between tests run in the different labs (95% lower confidence limit (LCL)  =  0.8182). The mean difference in max was less than 3.40 ml (kg/min) −1, within the variability expected for tests performed on different days, in different locations, using different metabolic carts. MRI performed at rest and following peak exercise stress indicated cardiac output increased from 5.1  ±  1.0 l min −1 to 16.4  ±  5.6 l min −1, LVEF increased from 65.2  ±  3.3% to 78.4  ±  4.8%, while RVEF increased from 52.8  ±  5.3% to 63.4  ±  5.3%. Regression analysis revealed a significant positive correlation between max and stroke volume ( R   =  0.788, P   =  0.006), while the correlation with cardiac output did not reach statistical significance ( R   =  0.505, P   =  0.137). max CPX testing can be effectively performed in the MRI environment, enabling direct combination of physiological data with advanced post-exercise imaging in the same test session.